2021
DOI: 10.4236/ce.2021.129163
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Use of Learning Strategies among Young Malaysian English as Second Language Learners

Abstract: Past studies have discerned gender disparity in language learning strategy (LLS) used among English as a Second Language (ESL) secondary schools and university students. However, very few studies have been done on learners in primary schools, particularly young Malaysian learners. This study, therefore, identifies frequently used learning strategies between genders in ESL classroom. A total of 30 young Malaysian learners at the age of 10 were selected through purposive sampling in a suburban area in Samarahan,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…In terms of study design, most of the reviewed studies are quantitative in nature using survey questionnaires (n = 16) (Adan & Hashim, 2021;Aziz & Shah, 2020;Chanderan & Hashim, 2022;Dawi & Hashim, 2022;Omar et al, 2020;Ghulamuddin et al, 2022;Hanafiah et al, 2021;Jais et al, 2022;John et al, 2021;Lim et al, 2021;Min et al, 2021;Nair et al, 2021;Ooi et al, 2021;Sani & Ismail, 2021;Vimalakshan & Aziz, 2021;Zamani et al, 2023) The qualitative studies (n = 6) comprise of literature review (Aziz & Kashinathan, 2021;Kathirvel & Hashim, 2020;Kehing & Yunus, 2021;Ramalingam et al, 2022), focus group interview (Othman et al, 2022), interview, and observation (Zahidi & Ong, 2023). Meanwhile, only one study (n = 1) uses a mixed-methods approach in study design (Kamaruzaman et al, 2023).…”
Section: Study Design and Subject Participantsmentioning
confidence: 99%
“…In terms of study design, most of the reviewed studies are quantitative in nature using survey questionnaires (n = 16) (Adan & Hashim, 2021;Aziz & Shah, 2020;Chanderan & Hashim, 2022;Dawi & Hashim, 2022;Omar et al, 2020;Ghulamuddin et al, 2022;Hanafiah et al, 2021;Jais et al, 2022;John et al, 2021;Lim et al, 2021;Min et al, 2021;Nair et al, 2021;Ooi et al, 2021;Sani & Ismail, 2021;Vimalakshan & Aziz, 2021;Zamani et al, 2023) The qualitative studies (n = 6) comprise of literature review (Aziz & Kashinathan, 2021;Kathirvel & Hashim, 2020;Kehing & Yunus, 2021;Ramalingam et al, 2022), focus group interview (Othman et al, 2022), interview, and observation (Zahidi & Ong, 2023). Meanwhile, only one study (n = 1) uses a mixed-methods approach in study design (Kamaruzaman et al, 2023).…”
Section: Study Design and Subject Participantsmentioning
confidence: 99%
“…The effectiveness of LLS as part of language acquisition (Sani & Ismail, 2021) has been impacted by the concept of language learning behaviours, which refers to the tendency of a learner to use the first language more frequently compared with the second language. Proactive language learning behaviour is more recommended in LLS because it improves the capacity of the learner to anticipate the challenges in the learning environment and respond to them in real-time (Kussin et al, 2018).…”
Section: Literature Review Language Learning Strategiesmentioning
confidence: 99%
“…Proactive language learning behaviour is more recommended in LLS because it improves the capacity of the learner to anticipate the challenges in the learning environment and respond to them in real-time (Kussin et al, 2018). Recent findings suggest that successful acquisition of LLS skills was majorly dependent on the extent to which learners prepared for and answered questions, had the courage to communicate irrespective of the circumstances and were oriented towards the use of songs (Sani & Ismail, 2021). A different perspective suggests that second language learning is not limited to grammatical competence, but other types of competence such as communication competence.…”
Section: Literature Review Language Learning Strategiesmentioning
confidence: 99%
“…It is spoken throughout the world, and it is taught as either English as Foreign Language (EFL) or English as Second Language (ESL). Sani & Ismail (2021) concluded that English is still relevant as a lingua franca students are expected to learn to survive the demands and the challenges of 21st-century education. Students in Malaysia learn English as a second language beginning from primary education until tertiary education.…”
Section: Introductionmentioning
confidence: 99%